2019
DOI: 10.21512/bbr.v10i2.5676
|View full text |Cite
|
Sign up to set email alerts
|

Product Development for Competitive Advantage of Micro, Small, and Medium Enterprises of Ikat Woven Fabric in Kediri

Abstract: The research aimed to provide the solutions for the method of selecting product development strategies based on competitive advantage criteria including Quality, Cost, Delivery, Service, and Morale (QCDSM). The research was done in Micro, Small, and Medium Enterprises (MSMEs) of Ikat woven fabric in which the collecting data used questionnaires for the customers. The questionnaire was regarding the criteria for competitive advantage for MSMEs of Ikat woven fabric in Kediri. The analysis methods applied Importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…This is also similar to Tadeo et al (2023) that offering ecologically safe products by ensuring them without potentially harmful and poisonous ingredients was commonly implemented green activity of MSEs in selected areas of Cavite. In addition, the utilization of recyclable and harmful-free materials may help retain the competitiveness of businesses (Ambarwati et al, 2019). and handy has the least percentage of 6.83 percent.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also similar to Tadeo et al (2023) that offering ecologically safe products by ensuring them without potentially harmful and poisonous ingredients was commonly implemented green activity of MSEs in selected areas of Cavite. In addition, the utilization of recyclable and harmful-free materials may help retain the competitiveness of businesses (Ambarwati et al, 2019). and handy has the least percentage of 6.83 percent.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Agustini et al (2021) emphasized that companies can take advantage of green products by differentiating products based on their characteristics. According to Ambarwati et al (2019), technical measures such as replacing plastic materials with recyclable materials, assuring the absence of harmful and poisonous elements in the raw materials, picking coloring supplies free of toxic and hazardous compounds, selecting a third party to supply the product, and using domestic raw materials may help MSMEs of Ikat woven fabric retain competitiveness. In the local setting, Tadeo et al (2023) found that MSEs in Cavite ensure that the products they sell are free from potentially harmful substances.…”
Section: Green Marketing Practices As a Strategy Of Msmesmentioning
confidence: 99%